Vključenost družbenih vidikov trajnosti v učna načrta za geografijo v osnovni šoli in splošni gimnaziji v Sloveniji - Banfi, Petra (Revija za geografijo, 2013)
The results of the analysis of curricula for geography in primary school and general secondary school are introduced from the view of participation of educational objectives and contents of social sustainability and principles of education for sustainable development which are a result of guidelines for education published by the Ministry for educational system and sports in Slovenia. We are seeing a sufficient participation of educational objectives from the view point of social sustainability and their relatively balanced number in comparison to the number of educational objectives in the field of environmental and economic sustainability. The treatment of content from the view of social sustainability depends upon teachers knowledge, personal awareness and own involvement. We have made suggestions in areas were educational objectives were slim or non-existent.
Keywords: družbeni vidik; geografija; geography; gimnazije; osnovne šole; pouk; sustainable development; trajnostni razvoj